Editorial - Vosloo, Robert (Stellenbosch Theological Journal, 2022)
In this 2021 edition of the Stellenbosch Theological Journal (STJ) we are proud to present 52 academic articles and one review article (the latter by Ernst Conradie on David Tracy’s recent two volumes of collected essays). All these articles undergone a rigorous peer review process. In addition, six book reviews and one interview are included.